The great firewall of China : how to build and control an alternative version of the internet - Griffiths, James T. (James Tomos), 1988- (London, England : Zed Books, 2020)
"Once little more than a glorified porn filter, China's 'Great Firewall' has evolved into the most sophisticated system of online censorship in the world. As the Chinese internet grows and online businesses thrive, speech is controlled, dissent quashed, and attempts to organise outside the official Communist Party are quickly stamped out. But the effects of the Great Firewall are not confined to China itself. Through years of investigation James Griffiths gained unprecedented access to the Great Firewall and the politicians, tech leaders, dissidents and hackers whose lives revolve around it. As distortion, post-truth and fake news become old news James Griffiths shows just how far the Great Firewall has spread. Now is the time for a radical new vision of online liberty"--Publisher's website
Introduction: Early warnings. Wall. Protests : solidarity from Hong Kong to Tiananmen -- Over the wall : China's first email and the rise of the online censor -- Nailing the jello : Chinese democracy and the Great Firewall -- Enemy at the gates : how fear of Falun Gong boosted the Firewall -- Searching for an opening : Google, Yahoo and Silicon Valley's moral failing in China -- Shield. Along came a spider : Lu Wei reins in the Chinese internet -- Peak traffic : Getting the Dalai Lama online -- Filtered : The firewall catches up with Da Cankao -- Jumping the wall : FreeGate, UltraSurf, and Falun Gong's fight against the censors -- Called to account : Silicon Valley's reckoning on Capitol Hill -- Sword. Uyghurs online : Ilham Tohti and the birth of the Uyghur internet -- Shutdown : how to take 20 million people offline -- Ghosts in the machine : Chinese hackers expand the Firewall's reach -- NoGuGe : the ignominious end of Google China -- The social network : Weibo and the last free-speech platform -- Gorillas in the mist : exposing China's hackers to the world -- War. Caught : the death of the Uyghur internet -- Key opinion leader : how Chinese trolls go after dissidents overseas -- Root and stem : the internet is more vulnerable than you think -- The censor at the UN : China's undermining of global internet freedoms -- Sovereignty : when Xi Jinping came for the internet -- Friends in Moscow : the Great Firewall goes west -- Plane crash : China helps Russia bring Telegram to heel -- One app to rule them all : how WeChat opened up new frontiers of surveillance and censorship -- Buttocks : Uganda's internet blackouts follow Beijing's lead -- Epilogue: Silicon Valley won't save you.
Includes bibliographical references (pages 321-373) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Internet -- Political aspects -- China; Freedom of speech -- China; Censorship -- China; Internet -- Government policy -- China; Gay & Lesbian studies; Electronic books